(untitled) (Серія: Історія. Політологія, 2021)
Проаналізовано механізм, реалізований місцевою партійно-радянською владою з метою залучення переселенців до колгоспів Донецької області. Приділено увагу співпраці із обласним управлінням держбезпеки, яке здійснювало моніторинг настроїв та намірів переселенців. Наведено факти соціальної взаємодії переселенців та вироблення ними практик виживання, що впливали на рівень результативності заходів місцевої влади у бік її зниження. The article contains analysis of the mechanism which was implemented by local party and soviet authorities to involve resettlers into kolkhozes of Donetsk region. Some of the documents analyzed by the author are introduced into scientific circulation for the first time. The author came to the conclusion that local party and soviet authorities implemented a number of agitational / propaganda measures, used moral and material incentives, implemented restrictions on unauthorized departure from the districts of the region. An important component of the mechanism was, first of all, their placement on the territory of kolkhozes. The material incentive was the endowment with a larger plot of homestead land and in some cases a priority in the provision of housing. However, homestead land mostly did not compensate for the land that the settlers had before moving. Land left in Poland and mentioned in the property descriptions was not evaluated or reimbursed. The level of wages on the collective farms was insufficient to support the family. The process of socialization of livestock caused a negative reaction. Under such conditions, neither moral encouragement nor a ban on leaving places of residence could deter the resettlers. The party leadership cooperated with the regional department of state security, which monitored the moods and intentions of the displaced persons. The level of effectiveness of local government measures was reduced by elements of social interaction of resettlers and their development of survival practices. The bulk of the settlers expressed their rejection of the collective farm system as such and "voted with their feet" against it. The resettlers mostly went to the western regions of Ukraine, hoping for the opportunity to run the farm individually. Some of them tried to return to Zakerzonia.